COMBINING ABILITY STUDY FOR SEED YIELD IN COWPEA [VIGNA UNGUICULATA (L.) WALP] - N. BHAVESH PATEL; R. T. DESAI; BHAVIN. N. PATEL; P. B. KOLADIYA (The Bioscan, 2012)
A study was carried out in half diallel fashion with twelve parents in cowpea. Parents were evaluated for estimation of gca and sca effects and variances for yield and yield contributing characters in four environments i.e., two season in late kharif 2010 (E1 and E2) and two season in late rabi 2011 (E3 and E4). The combining ability analysis revealed significant differences among the parents for all the traits indicating the presence of preponderance of dominance gene action for all the traits. The parents GC- 4 and Re - 101 recorded significant gca effects for seed yield per plant and most attributes. Among the hybrids, the best mean performance and significant sca effects for seed yield per plant were noticed for cross CPD-103 x Re-79 followed by GC-4 x CPD-105 and Rev7 x Re-79. These crosses need to be exploited and also one can explore the possibility of isolating transgressive segregants from the segregating generations of these crosses.